2017
DOI: 10.4154/gc.2017.06
|View full text |Cite
|
Sign up to set email alerts
|

Cluster defined sedimentary elements of deep-water clastic depositional systems and their 3D spatial visualization using parametrization: a case study from the Pannonian-basin

Abstract: According to the paper by (GRUND & GEIGER;2011;BORKA, 2016) this study area was characterized as sequences represent ing a prodeltaic submarine fan (Fig. 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…As it did not follow the normal distribution (Figure 2), the data had to be transformed. Box-Cox transformation was firstly employed, as with it a near normal transformation can be obtained (Horváth, Borka, & Geiger, 2017), but for any kind of γ value (Box & Cox, 1964), the results were unsatisfactory. Box-Cox transformation of the data with most favorable γ value of 0.4 is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…As it did not follow the normal distribution (Figure 2), the data had to be transformed. Box-Cox transformation was firstly employed, as with it a near normal transformation can be obtained (Horváth, Borka, & Geiger, 2017), but for any kind of γ value (Box & Cox, 1964), the results were unsatisfactory. Box-Cox transformation of the data with most favorable γ value of 0.4 is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…In Fig. 1 , innovation elements are the visual expression of innovation space [ 20 ], and the innovation base is the quantification of the spatial distribution of various innovation elements. Innovation network construction is the spatial expression of innovation cooperation networks formed by different innovation elements supported by different cooperation relationships.…”
Section: Methodsmentioning
confidence: 99%
“…An overview by AGAOGLU et al (2015) found that the laboratory work involved non-destructive and non-intrusive imaging techniques which used characterization and observation of multiphase flow system for greater accuracy. Therefore, a number of researchers (JANINA et al, 2017;SITTHIPHAT & SIAM et al, 2016;PENG et al, 2015;SA'ARI et al, 2015;KAMARUDDIN et al, 2011;NGEIN et al, 2011;FLORES et al, 2011;OOSTROM et al, 2007) have carried out various techniques and methods of non-destructive image analysis for liquid migration experiments. As stated by MAAS & HAMPEL 2006, an image analysis technique in the field of civil engineering was normally used to study the object flow absorption movement in boundary layers and liquid migration of small properties specific to the propagation of structure crack extension, and for this argument, a digital image processing technique was acceptable for use in the study of LNAPL migration in a fractured double-porosity soil.…”
Section: Introductionmentioning
confidence: 99%